Death from cancer at home: the carers' perspective. Issue 6872 (23rd January 1993) - Jones, R V; Hansford, J; Fiske, J
Abstract : OBJECTIVES--To collect information from principal carers of people who had died at home with cancer; to identify areas of support which need improvement. DESIGN--Semistructured interviews with carers two to four months after the death. SETTING--38 general practices in the Exeter, Torbay, and Plymouth health districts. SUBJECTS--207 carers. MAIN OUTCOME MEASURES--Services received by carers and quality of support. RESULTS--161 of 207 patients were aged 60 or over. 88 carers were aged under 60, 110 were 60-80, and 9 were > 80. Carers had difficulty in getting urgent professional help in only 15 out of 177 cases. 124 carers were not given advice on financial help and 174 were not told of support available from local charities. Although pain was well controlled, 25% of patients had no relief of other symptoms. Overall, 150 carers considered the support excellent, 45 good, 8 moderate, 2 poor, and 2 had no comment. CONCLUSIONS--Although care has improved in recent years, health professionals need to give carers more advice about help available outside health services. Domestic help was often needed earlier. Better appreciation of carers' problems is needed.